Nitrogen removal efficiency and pathways of the simultaneous nitrification and denitrification process under ultra-low oxygen conditions - Xiang, Yu (Environmental technology, 2025)
To explore strategies for further reducing aeration energy consumption in the simultaneous nitrification and denitrification (SND) process, an SND reactor was constructed to treat low carbon-to-nitrogen (C/N) ratio domestic wastewater under ultra-low dissolved oxygen (DO) conditions (DO < 0.05 mg·L⁻1). The effects of hydraulic retention time (HRT) and C/N ratio on nitrogen removal performance were systematically evaluated, and batch experiments were conducted to determine nitrification and denitrification rates. Under influent condition of 50.0 mg·L⁻1 ammonia and a C/N ratio of 2.2, the reactor maintained stable ultra-low DO levels, achieved effluent ammonia concentrations below 5.0 mg·L⁻1, and attained optimal SND efficiencies exceeding 80.0%. Although a shortened HRT destabilised performance, increasing the C/N ratio successfully restored nitrogen removal stability. Nitrification and denitrification rates ranged from 4.20-30.89 mg·L⁻1·h⁻1 and 1.57-21.92 mg·L⁻1·h⁻1, respectively, under C/N ratios from 2.2-8.0. High-throughput sequencing and metagenomic analysis revealed that heterotrophic nitrification and aerobic denitrification dominated nitrogen transformation, with microorganisms utilising low-energy nap and nirK enzymes to adapt to the ultra-low DO environment. These findings provide novel insights into energy-efficient nitrogen removal pathways under ultra-low oxygen conditions